A Proposed Project of Aluminum Foil and Copper Sheet as an Alternative Source of Energy: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Source of Energy is a power-producing technique that turns solar energy into electricity. Itmakes use of solar panels, which are frequently placed on buildings or gathered in solar farmsto speed up a process that turns solar light radiation into electricity. Copper Sheet is theelectrical conductor in many categories of electrical wiring. Also, the copper sheet is frequentlyutilized in the building and electrical appliance industries, while aluminum foil is made up of98.5% aluminum, and the remaining 2.5% is mostly silicon and iron for strength and punctureresistance.The overall means of the electrical engineers were 3.08 with a variance of 0.044; on the otherhand, the overall means of electricians were 3.21 with a variance of 0.046. The two groups ofrespondents obtained a T-computed value of -0.966, and the T-critical value is greater thanthe T-computed value, showing that there is a significant difference between the assessmentof the two groups of respondents.Based on the results of the study. The t-critical value is greater than the T-computed value,showing that there is a significant difference between the assessments of the two groups ofrespondents.
Keywords: Engineering